All Days 2008
DOI: 10.2118/115769-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Fracture Complexity, Reservoir Properties, and Fracture Treatment Design

Abstract: In many reservoirs fracture growth may be complex due to the interaction of the hydraulic fracture with natural fractures, fissures, and other geologic heterogeneities. The decision whether to control or exploit fracture complexity has significant impact on fracture design and well performance. This paper investigates fracture treatment design issues as they relate to various degrees and types of fracture complexity (i.e., simple planar fractures, complex planar fractures, and network fracture behavior), inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
99
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(107 citation statements)
references
References 74 publications
1
99
0
Order By: Relevance
“…Multiple long hydraulic fractures with uniform proppant distribution and sufficient fracture conductivity play an important role in achieving effective well stimulation and economic production of shale reservoirs [1][2][3][4][5][6][7]. Cipolla et al [8] studied the effect of proppant distribution in the fracture network on well performance and showed that proppant distribution significantly affects the fracture network conductivity and treatment design. Gu et al [9] presented that proppant transport in natural fractures has an important impact on critical fracture conductivity required for stimulation of shale reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple long hydraulic fractures with uniform proppant distribution and sufficient fracture conductivity play an important role in achieving effective well stimulation and economic production of shale reservoirs [1][2][3][4][5][6][7]. Cipolla et al [8] studied the effect of proppant distribution in the fracture network on well performance and showed that proppant distribution significantly affects the fracture network conductivity and treatment design. Gu et al [9] presented that proppant transport in natural fractures has an important impact on critical fracture conductivity required for stimulation of shale reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic Fracturing by Stimulated Reservoir Volume (SRV) [44] is a major technology to achieve commercial development of shale gas. However, the formation mechanism of effective fracture network has not been well understood.…”
mentioning
confidence: 99%
“…(15) leads to the final transient equation that is then used to update the nodal network pressures: (17) Once is equated then the fluid pressure terms in Eq. (13) and (14) are updated to the current problem time . In the present formulation the implicit solution initially advances ahead of the explicit solution of the structure field and during this stage the aperture and aperture strain rate terms are assumed constant over a single implicit solution time increment.…”
Section: Coupling Strategy: An Overviewmentioning
confidence: 99%
“…In broad terms the main numerical schemes appropriate for this class of problem include the FEM (Finite Element Method) [10,11,12] in its pure continuum form [13], the Discrete Fracture Network (DFN) geomechanical and continuum flow models [14], the Displacement Discontinuity Method (DDM) geomechanical and flow models [15,16,17], the combined FEM/DEM (Discrete Element Method) [18] technique plus the more recent Extended Finite Element Method (XFEM) [4,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation